Fatores associados a violência doméstica na gestação em adolescentes e adultas, em Feira de Santana, Bahia - Vidal, Luciana Maia Santos (2017)
The dissertation aims to analyze the prevalence and the associated factors of domestic violence in gestation at a referral maternity, in Feira de Santana, Bahia. It is a cross-sectional study with 324 women treated at the Women's Hospital after 24 hours postpartum. A bivariate analysis was performed with Pearson's Chi Square considering possible associations with presence of domestic violence and socioeconomic, demographic and gynecological-obstetric variables and drug use by relatives with p value <0.05 and multivariate analysis with logistic regression model With adjustments of variables that presented p value <0.05. Among the results, the prevalence of domestic violence was 21%, before gestation 48.5% and during gestation 51.5%. The proportions of the types of violence were psychological 34.3%, moral 23.8%, physical 19.3%, patrimonial (11.6%) and sexual (11%). The main offender was former companion. The presence of domestic violence indicated association with marital status (p 0.000), work away from home (p 0.001), occupation of women (p 0.002), women's financial dependency (p 0,000), partner's age (p 0.007), occupation (P0.032), number of births (p0.035), use of drugs by the former partner (p = 0.000), and psychological violence in the form of insult (OR = 0.44, 95% CI = 0.21 to 0.90, p = 0.026), and the mean age of the patients was significantly higher than that observed in the regression analysis. (OR = 0.43, 95% CI = 0.19-098, p = 0.046), presence of abortion (OR = 0.43, 95% CI = 0.19-096, p = 0.041). It is concluded that domestic violence in these findings incorporates gender relations within the family structure and should be investigated in prenatal services. From this perspective, it reflects the need for services and actions aimed at prevention in different personal, social and cultural perspectives of women, aggressors and families.